STRATEGIC ACTIONS OF THE EUROPEAN UNION REGARDING CLIMATE CHANGE: INTEGRATION PERSPECTIVES OF UKRAINE - Yamnenko, Tetiana; Hryhorovych, Maryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: consists in the theoretical justification of the international legal regulation of the Earth’s climate change issues, their problems and prospects. Research methods: logical, formal-dogmatic, comparative-legal, etc. Results: consists in the research and analysis of scientific and theoretical definitions of the historical perspective of the Earth’s climate change and the analysis of problems and prospects for the development of international legal mechanisms for the regulation of issues of the Earth’s climate change. Discussion: the possibilities of applying different doctrinal approaches to solving problematic issues of local ecology, including those related to the change of the Earth’s climate. In 2021, Ukraine continued its course of reforms and European integration. After the decision of the European Council to grant Ukraine the prospect of EU membership and the status of a candidate country, Ukraine needs to continue reforms, especially in the sphere of justice, the rule of law, the fight against corruption and fundamental rights. This includes the adoption and implementation of legislation on the procedure for the selection of judges to the Constitutional Court of Ukraine, the adoption of a general strategic plan for reforming the law enforcement sector, as well as the completion of the reform of the legislative framework regarding national minorities and the introduction of effective mechanisms for its implementation. The EU is going to continue to support Ukraine on its European path and, accordingly, combine this support with Ukraine’s post-war reconstruction efforts. In 2021, little progress was made in environmental reforms. However, in the field of combating climate change, Ukraine adopted and submitted its Nationally Determined Contribution to the Paris Agreement, as well as approved the National Strategy for Environmental Security and Adaptation to Climate Change. A dialogue between Ukraine and the EU regarding the European strategy of the «Green Deal» (The European Green Deal) and the «green» transformation of Ukraine was launched, and two extended working sessions were held in Brussels and Kyiv. Recently, the issue of ecology and methods of combating climate change has become increasingly acute.